No place to hide? The ethics and analytics of tracking mobility using mobile phone data - Taylor, Linnet (Environment and planning. D, Society & space, 2016)
This paper examines the ethical and methodological problems with tracking human mobility using data from mobile phones, focusing on research involving low- and middle-income countries. Such datasets are becoming accessible to an increasingly broad community of researchers and data scientists, with a variety of analytical and policy uses proposed. This paper provides an overview of the state of the art in this area of research, then sets out a new analytical framework for such data sources that focuses on three pressing issues: first, interpretation and disciplinary bias; second, the potential risks to data subjects in low- and middle-income countries and possible ethical responses; and third, the likelihood of ‘function creep’ from benign to less benign uses. Using the case study of a data science challenge involving West African mobile phone data, I argue that human mobility is becoming legible in new, more detailed ways, and that this carries with it the dual risk of rendering certain groups invisible and of misinterpreting what is visible. Thus, this emerging ability to track movement in real time offers both the possibility of improved responses to conflict and forced migration, but also unprecedented power to surveil and control unwanted population movement.